Heterologous prime–boost Zika virus vaccination induces comprehensive humoral and cellular immunity in mouse models - De Lorenzo, Giuditta; Tandavanitj, Rapeepat; Preciado-Llanes, Lorena; Sanchez-Velazquez, Ricardo; Prado Rocha, Raissa; Kim, Young Chan; Reyes-Sandoval, Arturo; Patel, Arvind H. (Frontiers in Immunology, 2025)
Zika virus (ZIKV) remained poorly studied until an outbreak in 2015 linked the virus to severe neurological disorders and congenital malformations. Currently, there are no antiviral drugs or vaccines available. We have previously demonstrated that a simian adenovirus vector vaccine (ChAdOx1 prMEΔTM) and a virus-like particle-based vaccine bearing E proteins locked in covalent dimers (VLP-cvD) are effective against ZIKV infection in animal challenge models. In this study, we further explored the efficacy of these vaccines, either individually or in combination, using a heterologous prime and boost vaccination strategy in mouse challenge models. Although the individual vaccines provided good protection levels, the heterologous prime–boost vaccination regimen (ChAdOx1 prMEΔTM followed by VLP-cvD) offered the most effective protection. This regimen elicited a strong cellular response and high levels of neutralising antibodies, which were attributed to ChAdOx1 prMEΔTM and VLP-cvD, respectively. Our findings support the use of combined vaccine technologies and offer valuable insights into the multifactorial protection achievable through heterologous vaccination. These results have important implications for the development of effective vaccination strategies against ZIKV and other emerging viruses.